Analisis Usahatani Tanaman stevia Pada Kelompok Tani Sumber Agung Sejahtera yang Menjalankan Kemitraan dengan PT. Industri Jamu dan Farmasi Sido Muncul Tbk. - Rivandie, Aldino; Prabowo, Rossi; Ni’mah, Lu’lu’a Ulyn; Fachriyan, Hilmi Arija (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This study analyzes the farming system of stevia (Stevia rebaudiana) under a partnership scheme between the Subur Agung Sejahtera Farmers Group and PT Industri Jamu dan Farmasi Sido Muncul Tbk. The main problem addressed is the uncertainty of market access and production costs faced by farmers in cultivating stevia as an alternative sweetener crop. The objective is to assess the cost structure, income, and economic benefits of the partnership. A descriptive analysis method with a mixed qualitative and quantitative approach was employed. Data were collected through surveys, structured interviews, and documentation, involving 10 farmers as respondents using a saturated sampling technique. The findings show that the total production cost per planting season (six months) amounted to IDR 184,786,667, consisting of fixed costs of IDR 13,696,667 and variable costs of IDR 171,090,000. The farming activities generated total revenue of IDR 375,000,000, resulting in a net income of IDR 190,213,333. These results indicate that the contractual partnership provides farmers with stable benefits, especially through guaranteed markets and fair prices. Strengthening cooperation with the company and improving production quality are recommended strategies to further increase farmers’ income.